Peningkatan Pengetahuan Perawat Tentang Pemberian Obat DOTS pada Pasien TB di RSU IPI Medan - Nixson Manurung (Universitas Muhammadiyah Manado, 2021)
TB is one of the 10 causes of death and the primary cause of infectious agents in the world. The prevalence of tuberculosis patients in 2020 amounted to 929 patients. Some of the influencing factors are behavioral factors, namely knowledge, attitude and behavior in the implementation of routine medication compliance. The method used was observational descriptive with 30 participants who were residents of Sampali Village, Percut Sei Tuan District. The PkM team provided the material in question: 1) Definition of tuberculosis disease, 2) Causes of tuberculosis disease, 3) Signs and symptoms of tuberculosis disease, 4) Complications of tuberculosis disease, and 5) Prevention of tuberculosis disease. After the implementation of the activity: 1) The majority of the understanding of tuberculosis (TB) is good as many as 25 people, 2) The causes of tuberculosis (TB) are mostly good as many as 27 people, 3) The signs and symptoms of tuberculosis (TB) are mostly good as many as 26 people, 4) The majority of tuberculosis (TB) complications are good as many as 27 people, and 5) Prevention of correct transmission of tuberculosis (TB) all participants have been able to as many as 27 people. The increase in knowledge and skills of participants is because the community has a great desire to treat and prevent dengue fever in family members at home.